KARAKTERISTIK NASABAH ASURANSI BNI LIFE INBRANCH DI KOTA PONTIANAK - B01108110, Aspera Rusanti (Jurnal Pembangunan dan Pemerataan, 2013)
This research was conducted in order to investigate the characteristics of BNI Life insurance customers Inbranch in Pontianak. The method used in thisresearch using adescriptive or using direch interviews and through questionnaires. The result BNI Insurance characteristics Inbranch in Pontianak showed that most were men between the ages of more than 40 years (50 percent) and had a job as a civil servant (PNS) of 53.6 percent and a Diploma/equal as much as 32.1 percent and earnings customers ranging from Rp. 3.000.000 Rp. 4.000.000 (57.1 percent). Age, occupation and income as the reason for its costumers in selecting the type of insurance. In addition, the benefits of this type of insurance is also considered a reason for customers. Keywords: Characteristics and BNI Life Insurance Inbranch